Looming Large or Seeming Small? Attitudes Towards Losses in a Representative Sample - Jonathan Chapman; Erik Snowberg; Stephanie Wang; Colin Camerer (Center for Economic Studies and ifo Institute (CESifo), 2022)
We measure individual-level loss aversion using three incentivized, representative surveys of the U.S. population (combined N = 3,000). We find that around 50% of the U.S. population is loss tolerant, with many participants accepting negative-expected-value gambles. This is counter to earlier findings-which mostly come from lab/student samples-and expert predictions that 70-90% of participants are loss averse. Consistent with the difference between our study and the prior literature, loss aversion is more prevalent in people with high cognitive ability. Loss-tolerant individuals are more likely to report recent gambling and to have experienced financial shocks. These results support the general hypothesis that individuals value gains and losses differently, although the tendency in a large proportion of the population to emphasize gains over losses is an overlooked behavioral phenomenon.
Keywords: C81; C90; D03; D81; D90; 330; loss aversion; DOSE; risk preferences; cognitive ability; negative shocks; gambling